Exercise-induced mitochondrial p53 repairs mtDNA mutations in mutator mice. Issue 1 (December 2015) - Safdar, Adeel; Khrapko, Konstantin; Flynn, James; Saleem, Ayesha; Lisio, Michael; Johnston, Adam; Kratysberg, Yevgenya; Samjoo, Imtiaz; Kitaoka, Yu; Ogborn, Daniel; Little, Jonathan; Raha, Sandeep; et al.
Abstract Background Human genetic disorders and transgenic mouse models have shown that mitochondrial DNA (mtDNA) mutations and telomere dysfunction instigate the aging process. Epidemiologically, exercise is associated with greater life expectancy and reduced risk of chronic diseases. While the beneficial effects of exercise are well established, the molecular mechanisms instigating these observations remain unclear. Results Endurance exercise reduces mtDNA mutation burden, alleviates multisystem pathology, and increases lifespan of the mutator mice, with proofreading deficient mitochondrial polymerase gamma (POLG1). We report evidence for a POLG1-independent mtDNA repair pathway mediated by exercise, a surprising notion as POLG1 is canonically considered to be the sole mtDNA repair enzyme. Here, we show that the tumor suppressor protein p53 translocates to mitochondria and facilitates mtDNA mutation repair and mitochondrial biogenesis in response to endurance exercise. Indeed, in mutator mice with muscle-specific deletion of p53, exercise failed to prevent mtDNA mutations, induce mitochondrial biogenesis, preserve mitochondrial morphology, reverse sarcopenia, or mitigate premature mortality. Conclusions Our data establish a new role for p53 in exercise-mediated maintenance of the mtDNA genome and present mitochondrially targeted p53 as a novel therapeutic modality for diseases of mitochondrial etiology.